ANALISIS DIAMETER GELEMBUNG PADA KERUGIAN TEKANAN ALIRAN FLUIDA - Rachmat Subagyo; I.N.G. Wardana; Eko Siswanto (ROTOR, 2016)
In the development of science studies have been conducted to observe the losses that occur in piping systems. During the fluid flowing through the pipe friction losses will occur between the fluid with the walls of the pipes, which are called by major losses. In general, the greater the loss of majorlosis on rough surfaces and can be reduced by using a more smooth surface such as glass, acrylic or with other coating materials. Gas bubbles that occur from the reaction of water with very influential magnesium in lowering the pressure in a turbulent flow. With the gas bubbles in the fluid flow creates the effect of two-phase flow. This study reviewed the effect of gas bubbles to the pressure drop (pressure drop) that occurs. The working fluid used is water that flowed through the channel with a square acrylic 18´9 mm size. The bottom of the channel is mounted ribbon mg powder grain size 160mm to create the effect of bubbles in the fluid flow. The powder iron (Fe) used as comparison with the same grain size. The results showed when the turbulent flow mg tape coating is more effective to reduce pressure losses due to flow into two phases and some bubbles that can survive will shrink the size of its diameter so it does not impede the flow rate. Keywords: Piping systems, major losis, bubbles of gas, two-phase flow, bubble effect.